Application of MODIS LST and Aurface Air Temperature Data for Snow Cover Analysis in Georgia - Tvauri, Genadi A.; Lomidze, Nino N.; Jinjolia, Tatiana D.; Koridze, Ketevan J. (Journals of Georgian Geophysical Society, 2017)
MODIS global Land Surface Temperature (LST) and Emissivity 8-day L3 Global 1 km and surface air temperature data measurements of different meteorological stations were used for analysis of snow cover in Georgia. It was shown that application of snow cover map correction algorithms based only MODIS Snow product data and algorithms with addition of LST and surface air temperatures give almost the same result. It was supposed that for snow cover map correction MODIS snow product data are quite enough and no additional correction is necessary.